Changes of Serum Zinc-α2-Glycoprotein Level and Analysis of Its Related Factors in Gestational Diabetes Mellitus. (19th February 2021) - Xu, Dongmei; You, Jie; Chen, Guixia; Su, Hongli; Zhang, Li; Cui, Lingling; Li, Zhonglei; Huang, Guoling; Feng, Caiying
Abstract : Previous studies have discovered that zinc- α 2-glycoprotein (ZAG) is related to insulin resistance and lipid metabolism. The aim of the study is to explore the change of serum ZAG and its related factors in gestational diabetes mellitus (GDM). Eighty newly diagnosed GDM patients were enrolled in the case group, and 80 normal pregnant women were selected as the control group. The differences of baseline data between the two groups were compared, and the change of serum ZAG level and its relationship with related indexes was analyzed. Compared to the control group, the level of serum ZAG in GDM women decreased (P < 0.001 ). What is more, the serum ZAG level of overweight and normal subjects in two groups was also found to have statistical differences. The Pearson correlation (or Spearman correlation) analysis showed that serum ZAG level was negatively correlated with FPG, FINS, HOMA-IR, and TG (all P < 0.05 ) and positively correlated with HDL (P < 0.05 ). Multiple linear regression showed that HDL and HOMA-IR were independent factors of serum ZAG (P < 0.05 ). The level of serum ZAG in patients with gestational diabetes mellitus decreased, and HDL and HOMA-IR are the influencing factors in the case group.